Skill Challenges in ICT Use among Economics Teachers at Tribhuvan University - Joshi, Bishnu Maya; Khatiwada, Shambhu Prasad; Pokhrel, Rajendra Kumar (Interdisciplinary Research in Education, 2024)
This paper analyzes the challenges in ICT proficiency among the economics teachers at Tribhuvan University in Nepal. This study uses a descriptive survey design to collect data from 404 Economics teachers at Tribhuvan University using a structured questionnaire. The statistical analysis indicates that gender, computer usage history, and additional income do not significantly impact skill challenges. It is found that skill-related barriers and proficiency issues hinder teachers' ability to effectively use ICT tools in the classroom, affecting instruction quality and confidence. Teachers faced challenges in effectively utilizing ICT, such as insufficient training, low confidence in ICT usage, and difficulties in integrating software into classroom activities. The job nature and home internet access significantly impact the challenges faced by permanent teachers and those without home internet access. The study emphasizes the need for professional development and internet access to enhance teachers' ICT skills, thereby improving education quality and fostering a more interactive learning environment.